Проблема обдарованості дітей з особливими освітніми потребами - Шульга, Альона; Білоус, Олена Василівна (My University, 2021)
The article is devoted to the problem of gifted children with special educational needs, which often goes unnoticed due to developmental disabilities. A theoretical analysis of the research problem is carried out, which involves an attempt to change existing stereotypes regarding the identification of gifted children with special educational needs and the further development of their abilities based on strengths. It is noted that this problem requires additional and troublesome research.
Keywords: проблема обдарованості дітей з особливими освітніми потребами; обдарованість; інклюзія; діти з особливи освітніми потребами